2006
DOI: 10.1021/cm051910o
|View full text |Cite
|
Sign up to set email alerts
|

XRD and XPS Study of Cu−Ni Interactions on Reduced Copper−Nickel−Aluminum Oxide Solid Solution Catalysts

Abstract: Copper−nickel−aluminum oxide solid solutions were reduced in hydrogen to produce alumina-supported copper−nickel alloy catalysts. XRD patterns of reduced oxides showed that the type of active metals which emerged upon reduction were sensitive to the reduction temperature and the copper content. Variations from +0.8 to +1 eV were found in the experimental Ni 2p3/2 binding energy (BE) of nickel in the solid solutions compared to the experimental Ni 2p3/2 BE of bulk nickel, attributed to the Ni−Ni arrangements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
133
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(148 citation statements)
references
References 30 publications
12
133
3
Order By: Relevance
“…9b and c, the binding energy (BE) of Cu (sp 2/3 ) was centered at 932.9 eV (Cu 0 species) and Ni (sp 2/3 ) at 852.7 eV (Ni 0 species), suggesting that Cu and Ni metals were produced under the reduction and activation step, these results were in accordance with XRD observations. Such BE values were slightly different from those reported in literature [35]. These differences indicated that some changes in electron density and chemical environmental of Cu and Ni took place in catalyst preparation.…”
Section: Investigation Of Catalyst Structurecontrasting
confidence: 83%
“…9b and c, the binding energy (BE) of Cu (sp 2/3 ) was centered at 932.9 eV (Cu 0 species) and Ni (sp 2/3 ) at 852.7 eV (Ni 0 species), suggesting that Cu and Ni metals were produced under the reduction and activation step, these results were in accordance with XRD observations. Such BE values were slightly different from those reported in literature [35]. These differences indicated that some changes in electron density and chemical environmental of Cu and Ni took place in catalyst preparation.…”
Section: Investigation Of Catalyst Structurecontrasting
confidence: 83%
“…Notably, the temperature at the maximum reduction peak was 644 K, which was lower than that for the reduction of unsupported pristine NiO (703 K) [33]. This phenomenon illustrated the interaction between nickel species and silica support [12].…”
Section: Reducibility Propertiesmentioning
confidence: 84%
“…The peaks at around 2e = 37. [33,35,38,[43][44][45]. Diffraction peaks of Ni species are not observed in all the XRD patterns.…”
Section: X-ray Diffractionmentioning
confidence: 91%
“…In addition, the difference in the position of reduction peaks reported here can be related to the fact that reduction peaks strongly depend on the particle dimension and the interaction strength between metal particles and the support. Previous work dealing with TPR studies on the reduction of Ni-Cu/y-Al 2 O 3 catalysts suggested that the addition of Cu to Ni precursors can dramatically decrease the reducing temperature of Ni oxides, and might markedly enhance the reducibility of the mixed oxide catalysts [23,38,39]. The promotion effect was stronger as the amount of Cu introduced increased [40][41][42].…”
Section: Tprmentioning
confidence: 95%